Centrality, rapidity and transverse momentum dependence of J/ψ suppression in Pb-Pb collisions at √ˢɴɴ = 2.76TeV - Abelev, B.; Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agócs, A.G.; Agostinelli, A.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahmad Masoodi, A.; et al. (Elsevier, 2014)
The inclusive J/ψ nuclear modification factor (Rᴀᴀ) in Pb–Pb collisions at √ˢɴɴ = 2.76 TeV has been measured by ALICE as a function of centrality in the e⁺e⁻ decay channel at mid-rapidity (|y| < 0.8) and as a function of centrality, transverse momentum and rapidity in the μ⁺μ⁻ decay channel at forward-rapidity (2.5 < y < 4). The J/ψ yields measured in Pb–Pb are suppressed compared to those in pp collisions scaled by the number of binary collisions. The Rᴀᴀ integrated over a centrality range corresponding to 90% of the inelastic Pb–Pb cross section is 0.72±0.06(stat.)±0.10(syst.) at mid-rapidity And 0.58 ± 0.01(stat.) ± 0.09(syst.) at forward-rapidity. At low transverse momentum, significantly larger values of Rᴀᴀ are measured at forward-rapidity compared to measurements at lower energy. These features suggest that a contribution to the J/ψ yield originates from charm quark (re)combination in the deconfined partonic medium.
Keywords: Relativistic heavy ion collisions; Quark gluon plasma; Quarkonium; J/ψ suppression; Experimental results; https://purl.org/pe-repo/ocde/ford#1.03.03